(untitled) (Research, Society and Development, 2022)
The study aims to analyze the strategies that workers use for the prevention and care of diseases related to working environments and conditions. Data collection included the application of a survey form with 270 workers residing in the municipalities of Health Region 28, in Rio Grande do Sul; and, at the same time, conducting interviews with six workers who have experienced work-related illnesses. The results of the study indicate, on the one hand, the limited recognition of work-related diseases by workers and the Specialized Services in Safety Engineering and Occupational Medicine; and, on the other hand, the different coping strategies used by workers in the face of work-related and experienced diseases. The analysis reaffirms the need for workers’ health to be socially consolidated through the recognition of the centrality of work in this process and the importance of their visibility both in the daily workplaces and in the discussion of public health policies.